Relationship of nutritional status and triglycerides/HDL-c index in adults cared for in a public hospital - Cachay Barboza, Edwar Paul (2022)
Objective. To determine the relationship between the nutritional status and the triglycerides /c-HDL ratio in adolescents treated in a public hospital. Materials and methods. Descriptive, cross-sectional, observational and retrospective study. Made up of 447 adults, 321 women and 126 men between 18 - 60 years of age who were treated by the nutrition service at Hospital I - Rioja - EsSalud during the period from March 2017 to June 2018. The status was determined nutrition according to the body mass index (BMI) and the TG/HDL-C ratio as a ratio of triglycerides and HDL cholesterol. Results. The mean age of the adults was 41.4 ± 12.7 years. A total mean TG/HDL-c index of 4.40 ± 1.45 was obtained, it was higher in women (4.62 ± 1.40) than in men (3.84 ± 1.44); likewise, obesity (4.76 ± 1.36) and overweight (4.57 ± 1.52) were the nutritional states that presented a higher index. A positive and significant correlation (r=0.397) with a p=0.000 was found between the Body Mass Index (BMI) and the TG/c-HDL index. Conclusion. There is a positive and statistically significant relationship between the body mass index and the TG/HDL-c ratio. The ratio of TG/c-HDL was higher in the nutritional status of obesity and overweight, exceeding the value of the population mean.